Building of adaptive information technology for computer systems diagnosing on presence of Trojan programmes - Savenko, O. S.; Lysenko, S. M. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Adaptive information technology for computer systems diagnosing on presence of Trojan programmes is developed in the paper, whose essence is in using behavioral patterns of classes of Trojans, which differs from the known ones by the fact that the process of diagnosis does not require the construction of its database, can detect new and unknown Trojans, and increases reliability and efficiency of diagnosis.